2015
DOI: 10.1530/jme-14-0321
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-regulated aminopeptidase in adipocyte is Cys-specific and affected by obesity

Abstract: Insulin-regulated aminopeptidase (IRAP, EC 3.4.11.3) in adipocytes is well known to traffic between high (HDM) and low (LDM) density microsomal fractions toward the plasma membrane (MF) under stimulation by insulin. However, its catalytic preference for aminoacyl substrates with N-terminal Leu or Cys is controversial. Furthermore, possible changes in its traffic under metabolic challenges are unknown. The present study investigated the catalytic activity attributable to EC 3.4.11.3 in HDM, LDM and MF from iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…The genetically obese Zucker rats (fa/fa) represent a model of insulin resistance and prediabetes characterized by hyperinsulinemia, hyperlipidemia and peripheral glucose intolerance which is caused largely by an impairment of insulin-stimulated glucose uptake into skeletal muscle, the major site of insulin-mediated glucose disposal (Ionescu et al, 1985;King et al, 1992). We and other authors have previously shown that obesity is associated with dysregulation of IRAP activity in adipose tissue and skeletal muscle along with reduced plasma oxytocin due to increased peptide degradation by peripheral tissues (Gajdosechova et al, 2014;Alponti et al, 2015). A study on IRAP-knockout mice showed protective effect of aminopeptidase deficiency against development of obesity (Niwa et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The genetically obese Zucker rats (fa/fa) represent a model of insulin resistance and prediabetes characterized by hyperinsulinemia, hyperlipidemia and peripheral glucose intolerance which is caused largely by an impairment of insulin-stimulated glucose uptake into skeletal muscle, the major site of insulin-mediated glucose disposal (Ionescu et al, 1985;King et al, 1992). We and other authors have previously shown that obesity is associated with dysregulation of IRAP activity in adipose tissue and skeletal muscle along with reduced plasma oxytocin due to increased peptide degradation by peripheral tissues (Gajdosechova et al, 2014;Alponti et al, 2015). A study on IRAP-knockout mice showed protective effect of aminopeptidase deficiency against development of obesity (Niwa et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have examined the role of IRAP in obesity and glucose handling using various animal models. Results have revealed that insulin regulated traffic of IRAP toward membrane fraction in adipocytes is disturbed by monosodium glutamate-induced obesity (Alponti et al, 2015) and IRAP deficiency in mice fed high-fat diet lead to prevention of development of obesity (Niwa et al, 2015). On the other hand, acute inhibition of IRAP aminopeptidase activity with specific inhibitor, HFI-419, does not affect glucose homeostasis in the streptozotocin-induced experimental rat model of diabetes mellitus (Albiston et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…53 It has been already demonstrated that MSG administration increases the cysteine levels in the plasma of the rats, which could be associated with insulin resistance and development of obesity. 55 In addition, the excess of G6P could favor pyruvate and acetyl-CoA generation, by stimulating the Krebs cycle. 52 The present findings demonstrate that MSG administration to male rats increased the hepatic citrate synthase activity, thus generating an excess of citrate that could be redirected to the triacylglycerol synthesis, demonstrated in this study by the increase in the triglycerides (TG) content.…”
Section: Discussionmentioning
confidence: 99%
“…Another possible explanation is that high levels of cysteine could deregulate the tyrosine metabolism and decrease the TAT activity in the liver . It has been already demonstrated that MSG administration increases the cysteine levels in the plasma of the rats, which could be associated with insulin resistance and development of obesity …”
Section: Discussionmentioning
confidence: 99%